AREAS OF CONTRIBUTION OF THE DISASSEMBLED ANALYSIS IN ACTIVATING THE COMPETITIVENESS OF THE INDUSTRIAL ENTITIES-APPLIED RESEARCH IN KARBALA CEMENT FACTORY - Mohammed Abed Kadhim; Ali Mohammed Thijeel AL-Mamouri (Scholars Digest Publishing, 2023)
There is a group of economic factors that affect the rationalization of costs, including intense competition between economic entities, which made them face to face with the danger of non-continuity and the deterioration of their competitive position if they did not reconsider in terms of applying the disassembled analysis approach as a modern strategic technology in the field of cost and administrative accounting, which can be Its role is for the economic entities to achieve rationalization of their costs in a way that helps achieve optimal utilization of resources, improve product processes, eliminate waste and loss, and as a result enhance competitive advantage by providing high quality products that meet customer requirements, in a timely manner, and at low prices. The research concluded a set of conclusions, the most important of which is that the Karbala Cement Factory, as the research sample, suffers from a waste of materials in addition to the lack of optimal use of resources. By applying these two techniques, the goal of rationalizing costs can be achieved, as well as providing useful information that helps the administration in making various decisions.
Keywords: disassembled analysis, activating the competitiveness, industrial entities